Induction Machine Flux Control during Transient Operation - Subba Rao Kulkarni, Suchet; Sharma, Mayur (My University, 2024)
Abstract This thesis investigates control methodologies for induction machines during transient operations, focusing on the implementation of active flux and torque current control strategies while emphasising energy efficiency and optimal performance. It begins by identifying the steady-state operating points that minimise copper losses, known as Maximum Torque per Ampere (MTPA) points. To find these points, the goal is to maximise the machine’s torque equation while considering the current and voltage equations as constraints. This is further solved as a constrained optimisation problem using MATLAB. Further, based on FOC principles the machine as well as the controller are modelled in inverse Γ-form dq reference frame using Simulink. To analyse the machine’s performance between two steady-state operating points, this work extends the application of MTPA to transient scenarios where rapid flux changes are necessary for responsive torque adaptation. The work explores the usage of active flux and torque control ideas by investigating the trade-offs involved in controlling isd and/or isq. The findings from this study are valuable in the development of control strategies for an induction machine in automotive drive systems. The study shows that using a PI-based flux controller accelerates the magnetisation and demagnetisation process. However, it is found that stable flux control is achieved in Field Weakening region when a field weakening controller is used. Furthermore, torque control mitigates the noticeable delay in torque production despite using active flux control during rapid and high torque demands. In these situations, additional compensation in isq is necessary to offset the lag. However, this comes with a trade-off: the copper losses increase due to deviations from MTPA trajectory in both isd and isq. Nevertheless, this strategy ensures an instantaneous torque response. Thus, employing a control strategy depends on multiple factors such as prioritising energy efficiency or performance, considering the machine’s operating state, and accounting for the resulting voltage and current constraints. Since no single strategy satisfies all requirements equally, the appropriate strategy should be chosen based on the preferred trade-off between energy efficiency and performance while also considering the machine’s operating conditions.
Keywords: Keywords: Induction Machine, MTPA, Transient control, Flux control, Torque control, Energy efficiency, trade-off analysis